2016
DOI: 10.1117/12.2268266
|View full text |Cite
|
Sign up to set email alerts
|

Mg2SixSn1-xheterostructures on Si(111) substrate for optoelectronics and thermoelectronics

Abstract: Thin (50-90 m) non-doped and doped (by Al atoms) Mg 2 Sn 0.6 Si 0.4 and Mg 2 Sn 0.4 Si 0.6 films with roughness of 1.9-3.7 nm have been grown by multiple deposition and single annealing at 150 o C of multilayers formed by repetition deposition of three-layers (Si-Sn-Mg) on Si(111) p-type wafers with 45 cm resistivity. Transmission electron microscopy has shown that the first forming layer is an epitaxial layer of hex-Mg 2 Sn(300) on Si (111) [110] have been found for the epitaxial layer. But inclusions of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In literature, there have been limited works on the MgSiSn thin films, as compared to the bulk form. Typically, a study on the very thin MgSiSn film (50 -90 nm) deposited on Si substrate was reported for optoelectronic and thermoelectric applications 6 . The used deposition technique, however, was a solid phase epitaxy (SPE), which is quite a complicated, expensive and hard-to-control method.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, there have been limited works on the MgSiSn thin films, as compared to the bulk form. Typically, a study on the very thin MgSiSn film (50 -90 nm) deposited on Si substrate was reported for optoelectronic and thermoelectric applications 6 . The used deposition technique, however, was a solid phase epitaxy (SPE), which is quite a complicated, expensive and hard-to-control method.…”
Section: Introductionmentioning
confidence: 99%